2008
DOI: 10.3122/jabfm.2008.04.070169
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antibiotics on Vulvovaginal Candidiasis: A MetroNet Study

Abstract: Purpose: Vulvovaginal candidiasis (VVC) is believed common after systemic antibiotic therapy, yet few studies demonstrate this association. In this pilot study, we evaluate the effect of short-course oral antibiotic use on VVC.Methods: Nonpregnant women aged 18 to 64 years who required >3 days oral antibiotics for nongynecological diseases were recruited from a family medicine office. Age-matched (؎5 years) women seen in the same clinic for noninfectious problems were recruited as controls. The main outcomes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 42 publications
1
62
3
Order By: Relevance
“…The prevalence of VVC was 80% among antibiotics users, as eight out of the ten women who had taken antibiotics recently had VVC compared with 31% among nonusers (28 out of 90), which is highly suggestive of a positive correlation between recent antibiotics ingestion and development of vulvovaginal candidiasis. This relationship was also statistically signifi cant in agreement with several other studies that have linked candidiasis to ingestion of antibiotics [29][30][31]. A similar relationship was also found with bacterial vaginosis (70% vs. 34%), which was signifi cant as well.…”
Section: Discussionsupporting
confidence: 80%
“…The prevalence of VVC was 80% among antibiotics users, as eight out of the ten women who had taken antibiotics recently had VVC compared with 31% among nonusers (28 out of 90), which is highly suggestive of a positive correlation between recent antibiotics ingestion and development of vulvovaginal candidiasis. This relationship was also statistically signifi cant in agreement with several other studies that have linked candidiasis to ingestion of antibiotics [29][30][31]. A similar relationship was also found with bacterial vaginosis (70% vs. 34%), which was signifi cant as well.…”
Section: Discussionsupporting
confidence: 80%
“…In the current study, there was no significant correlation between the incidence of Candida-culture positive from women who previously used oral contraceptives (P= 0.146) or antibiotics (P=0.128) and those who did not, whereas other studies showed significant correlation in this regard (Yusuf et al, 2007;Xu et al, 2008;Bahram et al, 2009). Also some reports found no evidence of an association between antibiotic-drugs and symptomatic VVC, whereas others concluded otherwise (Xu et al, 2008).…”
Section: Discussioncontrasting
confidence: 50%
“…Also some reports found no evidence of an association between antibiotic-drugs and symptomatic VVC, whereas others concluded otherwise (Xu et al, 2008). This discrepancy is apparently due to differences in size of studied women subjects, duration and types of used contraceptives or antibiotics, as well as methods of yeast-detection.…”
Section: Discussionmentioning
confidence: 66%
“…Likewise, Glover and Larsen [24] concluded that the extensive antibiotic use posed little risk for the development of fungus infection. In the same line, Jinping et al [25] hypothesized that baseline fungus culture obtained from vagina requiring antibiotic therapy may develop symptomatic vulvovaginal mycotic infection after antibiotic therapy. Similarly, Bluestein et al [26] reported 35% fungus colonization at baseline increased to 50% after 10 d of antibiotic therapy.…”
Section: Discussionmentioning
confidence: 95%